Experimental and Theoretical Study of Bisphenol a Migration from Polycarbonate into Regulated Eu Food Simulant - Guarda-Moraga, A; Valenzuela-Bascunan, X; Romero-Figueroa, J; Galotto-Lopez, M; Torres-Mediano, A (Springer Verlag, 2015)
The specific migration of [2,2-bis(4 hydroxyphenyl) propane] from polycarbonate films into ethanol 50 % food simulant was studied. A phenomenological model based on a resistances-in-series system was resolved through the regula falsi algorithm. The diffusion–convection model was not able to describe the BPA concentration change as a function of time after 40 h, since an equilibrium condition with a plateau is not achieved. BPA generation due to PC hydrolysis produces an increase in BPA concentration. The continuous generation of BPA can be described by a generation–diffusion–convection model, where BPA generation obeys to a pseudo-zero-order reaction. © 2014, Springer-Verlag Berlin Heidelberg.